Museum Van Bommel - Van Dam Venlo : Een beeld van de collectie. - Alberigs, L. M. (Venlo : Museum Van Bommel Van Dam, 1971)
Chagall, Marc ; Picasso, Pablo ; Manessier, A. ; Bissière , Zao-Wou-Ki ; Friedländer, Johnny ; Lurçat, J. ; Campigli, M. ; Adam, H.G. ; Goerg, Ed ; Dufy, Raoul ; Boode, Dirk ; Bauer, Marius ; Coubine, O. ; etc.
Nederlands
boek